Effect of Codoping Cl Anion and 5-AVA Cation on Performance of Large-Area Perovskite Solar Cells with Double-Mesoporous Layers - Yaxian Pei; Xiaoping Zou; Yingxiang Guan; Gongqing Teng (International Journal of Photoenergy)
For the perovskite solar cells (PSCs), the performance of the PSCs has become the focus of the research by improving the quality of the perovskite absorption layer. So far, the performance of the large-area PSCs is lower than that of small-area PSCs. In the paper, the experiments were designed to improve the photovoltaic performance of the large-area PSCs by improved processing technique. Here we investigated the optoelectronic properties of the prototypical CH3NH3PbI3 (MAPbI3) further modulated by introducing other extrinsic ions (specifically codoped Cl− and 5-AVA+). Moreover, we used inorganic electron extraction layer to achieve very rapid photogenerated carrier extraction eliminating local structural defects over large areas. Ultimately, we fabricated a best-performing perovskite solar cell based on codoping Cl anion and 5-AVA cation which uses a double layer of mesoporous TiO2 and ZrO2 as a scaffold infiltrated with perovskite and does not require a hole-conducting layer. The experiment results indicated that an average efficiency of double-mesoporous layer-based devices with codoping Cl anion and 5-AVA cation was obtained with exceeding 50% enhancement, compared to that of pure single-mesoporous layer-based device.